2015
DOI: 10.1183/13993003.02052-2014
|View full text |Cite
|
Sign up to set email alerts
|

The striated muscles in pulmonary arterial hypertension: adaptations beyond the right ventricle

Abstract: Pulmonary arterial hypertension (PAH) is a fatal lung disease characterised by progressive remodelling of the small pulmonary vessels. The daily-life activities of patients with PAH are severely limited by exertional fatigue and dyspnoea. Typically, these symptoms have been explained by right heart failure. However, an increasing number of studies reveal that the impact of the PAH reaches further than the pulmonary circulation. Striated muscles other than the right ventricle are affected in PAH, such as the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 83 publications
(122 reference statements)
0
32
0
Order By: Relevance
“…Skeletal muscle dysfunction and severe, chronic deconditioning may be an underestimated problem in PAH patients [12]. With respect to the Fick equation, skeletal muscle function during exercise relates to Ca-vO 2 , as remaining organ oxygen demand is assumed to be relatively constant during exercise, and an increase in oxygen extraction is mainly caused by increased skeletal muscle metabolism.…”
Section: Cardiovascular Response To Exercise In Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle dysfunction and severe, chronic deconditioning may be an underestimated problem in PAH patients [12]. With respect to the Fick equation, skeletal muscle function during exercise relates to Ca-vO 2 , as remaining organ oxygen demand is assumed to be relatively constant during exercise, and an increase in oxygen extraction is mainly caused by increased skeletal muscle metabolism.…”
Section: Cardiovascular Response To Exercise In Pahmentioning
confidence: 99%
“…Unlike muscles, which may increase in strength/endurance with increased loading, there is mixed evidence of respiratory muscle weakness in pulmonary hypertension [12,29,31,32]. Although this does not lead to exercise limitation, it is conceivable, although unproven, that this may contribute to the sensation of dyspnoea.…”
Section: Respiratory Response To Exercise In Pahmentioning
confidence: 99%
“…Skeletal muscle abnormalities have been demonstrated in patients with pulmonary arterial hypertension PAH [79][80][81] . As in COPD, skeletal muscle weakness in PAH patients leads to increased dyspnoea, fatigue, poor exercise tolerance, and impaired quality of life [79][80][81] .…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…As in COPD, skeletal muscle weakness in PAH patients leads to increased dyspnoea, fatigue, poor exercise tolerance, and impaired quality of life [79][80][81] . Similarly, a switch to a less fatigue-resistant phenotype (lower proportions of slowtwitch fibres) and increased anaerobic metabolism have been demonstrated in the lower limb muscles of patients with PAH [82][83][84] .…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Finally, it is important to point out that use of non-pharmacological interventions like participation in exercise training programs has been advocated for the patient with PAH as they have been shown to increase exercise capacity, pulmonary hemodynamics, and health-related quality of life 12 . This is relevant in light of recent studies that have shown atrophy and dysfunction of striated muscles associated with the respiratory and musculoskeletal systems 13 .…”
Section: Introductionmentioning
confidence: 97%